Financial cost-benefit analysis for the establishment of areas free from and areas of low pest prevalence of Bactrocera dorsalis (Hendel) in South Africa - Van Zyl, Jo Bridget (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.